Virtual Laboratories Meet Eco-Critical Literacy: A Bibliometric Mapping of Science Education Landscapes - Erni Dwiastuti; Asri Widowati (Assyfa Learning Journal, 2026)
The rapid advancement of digital technology has transformed science education through virtual laboratories, offering interactive and safe learning environments. However, comprehensive studies mapping the specific convergence between virtual laboratory-based science learning, critical thinking, and eco-critical literacy remain limited. This study aims to map the research landscape of virtual laboratory-based science education related to critical thinking skills and environmental awareness through a bibliometric approach. Data were collected from Google Scholar using Publish or Perish, yielding 995 relevant publications analyzed via VOSviewer version 1.6.20 through co-occurrence, network, overlay, and density visualizations. The findings indicate that virtual laboratories have become a prominent theme in contemporary science education, with dominant keywords including virtual laboratory experiment, science process skill, critical thinking skill, scientific literacy, and environment. Network analysis identified six major research clusters representing learning outcomes, skills development, pedagogical approaches, emerging technologies, methodologies, and contexts. Furthermore, overlay and density visualizations revealed a significant shift from mere technology implementation toward competency development and sustainability-oriented learning, highlighting artificial intelligence, virtual reality, augmented reality, and environmental education as emerging themes with substantial future potential. In conclusion, this study contributes to a better understanding of virtual laboratory research development and proposes future research directions focusing on intelligent learning, immersive environments, critical thinking enhancement, and sustainability-oriented science education to foster eco-critical literacy.